The pat a pengampong a ranao a study on the emergence of Lanao Sultanates in the 21st century - Cayamodin, Jamel R. 1983- (Quezon City University of the Philippines Diliman, 2007)
This study entitled, THE PAT A PENGAMPONG SA RANAO: "A Study on the Emergence of Lanao Sultanate in the 21st Century" intends to emphasize the major factors of the coming forth of the many claimants to the throne of the Lanao Sultanates and the emergence of the number of the Sultans in every Royal House in the Pat a Pengampong a Ranao today.The author endeavors to pursue the following objectives: to find out the major factors which led to the emergence of the many Sultans in Lanao today; to evaluate the influence of the emergence of these many Sultans upon the political development of Lanao and in the promotion of Islamic-Traditional governance; to assess the effect of the emergence of these Sultans upon the Institution itself; to emphasize the coping mechanisms initiated by the Meranaos in dealing with these many Sultans; and, to analyze the Islamicity of Meranao Sultanates -- including the coping mechanisms. The study highlights the influence of the many Sultans on the Meranaos, their society, and on their politico religious condition. It examines methodically how this phenomenon affects the institution itself and hinders the promotion of Islamic-Traditional governance as Lanao Sultanate institution's primary goal. The study also shows the existing civil society groups that initiates coping mechanism in dealing with this new phenomenon in order to bring back the origin of the Sultanate institutions in the Pat a Pengampong a Ranao as manifested in the olden days. The study is significant in the realm of the academe in filling the gap of many literature that have for their subjects the Lanao Sultanate institution; it reawakens the opulence's struggle to attain the restoration of the Lanao Sultanates to their origin; and finally for the Maranao leaders, intellectuals and law makers to help being to an unusual enthronements to unearth an ideal Muslim Ummah and a peaceful Meranao society.
Vita.
"April 2007."
Thesis (M.A. Islamic Studies)--University of the Philippines Diliman.
Keywords: Lanao del Sur(Philippines) -- History; Sultans -- Philippines -- Lanao del Sur